The Influence Of The Binder On Quality Of Rendang Boleces Of Chicken Afkir - Aztia Rima Annisa; Rahmi Holinesti (Universitas Negeri Padang, 2020)
The background of this research is there has not been the use of chicken afkir especially in West Sumatera. Chicken afkir is an egg-laying hen that is no longer productive to lay eggs due to the age of this old chicken. The focus of this research is to know the effect of binding materials on the quality of rendang boleces of chicken afkir in terms of shape, color, aroma, texture and taste. This type of research is pure experimentation, with the aim of revealing both influences and differences between two different variables. The research design used is the Completed Randomized Design. The type of data used is primary data obtained directly from 5 trained panelists by filling in the organoleptic test format. For hypothetical testing, the study used statistic t test, with a significant level of 5 % (=0,05). The results showed that there was no significant influence on the use of tapioca flour as binding agent with glutinous rice flour as binding agent on the quality of the shape, color, aroma, texture and taste of boleces of chicken afkir. From the statement, it is concluded that Ho was accepted due to the t count < t table.